Potential use of freshwater insect larvae in river biological monitoring: a systematic review - Ahmad, Abas Kutty; Hani Nazirah Suhaimi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Freshwater insect larvae, also known as macroinvertebrates, are potential bio-indicators for water quality monitoring in Malaysia, as they were reported to have extensive density and distribution in Malaysian river ecosystems. The indices formed based on macroinvertebrate biogeographical data exhibited a good conjunction with the national water quality standard (NWQS) and water quality index (WQI) for monitoring the water quality in Malaysia. With a significant sensitivity, macroinvertebrates provide usable responses to environmental changes, which are highly similar to the water quality indices. Even these indices can provide an assessment of river quality faster and cheaper. This systematic study was conducted to demonstrate the potential use of macroinvertebrate-based available indices. Selected features evaluated are taxonomy level, type of indices, study area, and the similarity of the result with WQI. The survey was conducted using the Systematic Reviews and Meta-Analyses (PRISMA) system consisting of eight stages of analysis. Manuscript searches have been conducted using Scopus and Web of Science search engines. Searched manuscripts were filtered according to the scope of the study and only manuscripts that meet the inclusion criteria were selected. A total of 184 manuscripts were found throughout the search and only 36 manuscripts were accepted for further analysis. Subsequently, the extraction of information from selected manuscripts was carried out, and each chosen issue's division was arranged in Microsoft excel. This study found that the most widely used biotic indices in Malaysia were Biological Monitoring Working Party (BMWP) followed by Average Score Per Taxon (ASPT), and the Family Biotic Index (FBI), while the most used diversity indices were the Shannon diversity index (H’) followed by the Margalef richness index (R’) and the Pielou evenness index (J). The family level was the most frequent for indices calculations compared to genus and species. Among all the indices used, BMWP was statistically proven to have the closest result to WQI, followed by the FBI, H’ and R’. The high similarity value with WQI proves that the macroinvertebrate's biotic and diversity indices are very significant in monitoring river ecosystem quality in Malaysia even if only at the family taxonomic level. These indices also showed small variations even in different rivers, demonstrates the suitability of many types of rivers in Malaysia.